PENGARUH PEMBAYARAN DIGITAL DAN KERENTANAN KEUANGAN YANG DI MODERASI LITERASI KEUANGAN - Covery Adi Saputro; Ujang Suherman; Rengga Madya Pranata (Journal Of Resource Management, Economics And Business, 2024)
Purpose: To determine the effect of digital payments and financial literacy on financial vulnerability in UBP Karawang management students. Research Methodology: Quantitative research; population: UBP Karawang management students (Class of 2020-2023, n=1948); sample: 95 students; data collection via Google Forms; analysis using moderated regression analysis. Results: Digital payments did not significantly affect financial vulnerability; 88.7% influence of digital payments and financial literacy on financial vulnerability; financial literacy moderates the relationship. Limitations: The study is limited to UBP Karawang management students, which may affect generalizability. Contribution: Useful for fields such as financial education, digital finance, and consumer behavior in Indonesia.